2010
DOI: 10.1007/s10404-010-0708-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on microchannel oil-in-water emulsification

Abstract: Microchannel (MC) emulsification is a promising technique to produce monodisperse emulsions by spontaneous interfacial-tension-driven droplet generation. The purpose of this study was to systematically characterize the effect of temperature on droplet generation by MC emulsification, which is a major uncharted area. The temperature of an MC emulsification module was controlled between 10 and 70°C. Refined soybean oil was used as the dispersed phase and a Milli-Q water solution containing sodium dodecyl sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…Figure 3 illustrates the relationship of the equilibrium interfacial tension (γ eq ) between the two phases at each temperature from 10℃ to 70℃. γ eq for the sodium oleate-containing system increased exponentially as T C increased, similar to the results for the sodium dodecyl sulfate-containing system (Butron Fujiu et al, 2010). In contrast, γ eq for the systems containing Tween 20 and PGM decreased exponentially as T C increased.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Figure 3 illustrates the relationship of the equilibrium interfacial tension (γ eq ) between the two phases at each temperature from 10℃ to 70℃. γ eq for the sodium oleate-containing system increased exponentially as T C increased, similar to the results for the sodium dodecyl sulfate-containing system (Butron Fujiu et al, 2010). In contrast, γ eq for the systems containing Tween 20 and PGM decreased exponentially as T C increased.…”
Section: Resultssupporting
confidence: 78%
“…The equilibrium interfacial tension across the two phases was measured by the pendant drop method using a Full Automatic Interfacial Tensiometer (PD-W, Kyowa Interface Sciences Co., Ltd., Saitama, Japan). The contact angle of the dispersed phase to the channel wall was measured using a new MC array method proposed by Butron Fujiu et al (2010). Prior to each contact-angle measurement, the dispersed phase was introduced into hydrophilic channels (20-μm wide, 5-μm deep, and 2000-μm long) filled with the continuous phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b(i), the interfacial shape was kept symmetric to the center line of the MC. These results are typical behaviors for successful, stable droplet generation by MC emulsification (Butron Fujiu et al, 2011a). Figure 3a illustrates the variation of the d av and CV of the resultant O/W emulsion droplets stabilized by SDS during the continuous MC emulsification.…”
Section: Methodsmentioning
confidence: 74%
“…Butron Fujiu et al (2011a;2011b) reported that the maximum generation rate of uniformly sized soybean oil droplets stabilized by nonionic Tween 20 is lower than those stabilized by anionic SDS when using a hydrophilic silicon MC array plate. Kobayashi et al (2012) also reported some affinity between the dispersed phase covered by Tween 20 molecules and the plate surface, as the absolute ζ-potentials of soybean oil droplets stabilized by Tween 20 and the chip surface are markedly lower than those for the SDS-containing system.…”
Section: Resultsmentioning
confidence: 99%